A partially inactivating mutation in the sodium-dependent lysophosphatidylcholine transporter MFSD2A causes a non-lethal microcephaly syndrome - Alakbarzade, Vafa (NATURE PUBLISHING GROUP, 2020)
10.1038/ng.3313